POTENSI EKSTRAK ETANOL BAWANG MERAH (Allium ascolonicum L.) DAN GARAM NaCl MENURUNKAN LUAS AREA SERTA MENINGKATKAN KONTRAKSI JARINGAN LUKA BAKAR RINGAN - Sukadana, I M.; Rahayu, S.; Melli, Melli (Jurnal Kimia (Journal of Chemistry), 2019)
Burns is a skin response and subcutaneous tissue to temperature or thermal trauma that affects skin damage. The weight or severity of tissue damage from burns is influenced by several factors including deep burns, burns area, burn location, general body health, injury mechanism and age. The area of ??burns and the percentage of wound contractions is an indicator of the healing process of minor burns. This study used 25 wistar rats divided into 5 treatment groups with randomized posttest only control group design as follows; K: given vaseline treatment (negative control), K p : given bioplacenton treatment (positive control), P 1 : given salt treatment at 7.5% concentration in vaseline, P 2 : given onion extract treatment at 40% concentration in vaseline, and P 3 : given a mixture of onion extract 40% and kitchen salt at a concentration of 7,5% in vaseline. The result of One-Way ANOVA and Post Hoc Test LSD using SPSS for Windows version 19 shows P 2 treatment group is onion extract of 40% give the best result concentration of onion extract so it is very potential to be developed further as light burning agent compared to P 1 and P 3 treatment group because of its ability to decrease the area of ??340,79 mm 2 on the first day to 11,75 mm 2 and increased wound contraction by 81,59% at the end of treatment